Cambridge international AS and A level computer science coursbook - Langfield ,Sylvia (Cambridge University Press , Cambridge, 2015)
"Cambridge International AS and A Level Computer Science Coursebook delivers an accessible guide to theoretical and practical skills in Computer Science, with a clear progression of tasks that help to consolidate and develop knowledge. Cambridge International AS and A Level Computer Science Coursebook offers students detailed descriptions of the concepts, reinforced with examples that outline complex subject matter in a clear way. Alongside fundamental definitions, higher level programming skills are developed through the explanation of processes and consolidated by practical exam-type questions for students to attempt."-- Publisher description
A level